Precision Medicine: A Comprehensive Review of Advances and Challenges on Implementaion Integrated Management of Childhood Illness - Joaquim Pinto; Eugenia Carvalho de Araujo; Carlos Boavida Tilman; Adelina Pinto; Manuel Fransisco da Costs (Medical Studies and Health Journal (SEHAT), 2024)
Precision medicine is a rapidly growing paradigm in the understanding of disease, especially in pediatric medicine. This article evaluates significant advances in genomics and gene-based technologies, and their impact on personalized diagnosis and therapy for children. The integration of genetics with epidemiology opens up new opportunities in understanding gene-environment interactions and disease disparities, which have a direct impact on childhood disease management. Nevertheless, challenges such as equitable access to genetic innovation worldwide still need to be overcome. Recommendations include improved research methods, cross-country collaboration, as well as assessment of long-term effects and greater patient involvement in clinical decision-making.